Abnormalities of the First Three Steps of Gait Initiation in Patients with Parkinson's Disease with Freezing of Gait - Yohei Okada; Takahiko Fukumoto; Katsuhiko Takatori; Koji Nagino; Koichi Hiraoka (Parkinson's Disease)
The purpose of this study was to investigate abnormalities of the first three steps of gait initiation in patients with Parkinson's disease (PD) with freezing of gait (FOG). Ten PD patients with FOG and 10 age-matched healthy controls performed self-generated gait initiation. The center of pressure (COP), heel contact positions, and spatiotemporal parameters were estimated from the vertical pressures on the surface of the force platform. The initial swing side of gait initiation was consistent among the trials in healthy controls but not among the trials in PD patients. The COP and the heel contact position deviated to the initial swing side during the first step, and the COP passed medial to each heel contact position during the first two steps in PD patients. Medial deviation of the COP from the first heel contact position had significant correlation with FOG questionnaire item 5. These findings indicate that weight shifting between the legs is abnormal and that medial deviation of the COP from the first heel contact position sensitively reflects the severity of FOG during the first three steps of gait initiation in PD patients with FOG.